The Influence of Organizational Culture on Employee Retention: The Mediating Role of Job Satisfaction - Pant , Dinesh Kumar (Journal of Entrepreneurship & Management Studies, 2025)
This study aims to analyze how organizational culture affects employee retention in service sector organizations in Surkhet District, with a special emphasis on how job satisfaction acts as a mediator in this relationship. The research adopted a causal-comparative research design. Data collection technique involved a convenience sampling, yielding a sample of 350 employees from diverse service sector organizations situated in Surkhet. Structural equation modeling, facilitated by Smart PLS (Partial Least Squares), served as the principal analytical instrument. The findings revealed that organizational culture significantly influences employee retention. Additionally, job satisfaction was identified as a critical mediator, strengthening the relationship between organizational culture and employee retention. A positive organizational culture not only directly enhances retention but also indirectly contributes to it by fostering higher levels of job satisfaction among employees. The study’s results are limited by its use of convenience sampling in a single district, which may not represent all employees or service sectors elsewhere leaving the room for further research. The findings hold significant implications for managers and policymakers, suggesting that prioritizing supportive organizational practices and aligning strategies with employee well-being can help service sector organizations in Surkhet achieve sustainable retention outcomes and maintain a competitive advantage in the market.